PRODUKTIVITAS JAM KERJA EFEKTIF PEKERJA PADA PEKERJAAN PLESTERAN DAN ACIAN TERHADAP ELEVASI DINDING PADA PROYEK PERUMAHAN GRAHA PERMATA KOTA - , ANGGA DICKY SUSANTO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Productivity in the world of construction is very important factor. Labour productivity is the ability of labour to produce goods or services within a certain time unit. The level of productivity of a project is influenced by several factors. This research purpose to know the stage of labor productivity at stretch coat and finish coat about the wall elevation. This study was conducted by observing the worker at the housing project. Processing observational data by calculating the stage of every productivity labour. The results of this study is the stage of labour productivity in a day. The value of productivity compared to variable height wall, worker age, work experience, and education the last worker.